Some aspects of judicial review in constitutional production Jenny: theory and practice. - Rozwadowski, Volodymyr (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article examines the problems of the contradictions of the Constitution of Ukraine with legal acts that are the subject of constitutional control. The types (approaches) of control carried out by the Constitutional Court of Ukraine by normative legal acts, international agreements, decisions of referendums are analyzed.